State economies, metropolitan governance, and urban-suburban economic dependence - Post, Stephanie Shirley; Stein, Robert M. (2000)
Previous research finds that central-city and suburban indicators of economic development are strongly related. Missing from previous research, however, is an empirical test of the expected relationship between urban-suburban economic dependence and the structure of metropolitan-area governance. In addition, the impact of the state economy on this relationship has not been fully examined. The authors replicate previous research that demonstrates a relationship between the change in central-city and suburban per capita income. Then they test whether this relationship is solely a function of the state economy and if it is affected by the structure of metropolitan area governance. - Reproduced
Keywords: Metropolitan government; Economic and social development; Local government